(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of Human Resource (HRM) management in improving employee productivity in the digital era. The method used is a Systematic Literature Review (SLR) by analyzing 15 relevant scientific articles from 2020–2026 obtained through Google Scholar and SINTA. Data were analyzed using descriptive qualitative analysis techniques through the stages of extraction, categorization, synthesis, and interpretation of research findings to identify patterns and relationships between the variables studied. The results show that HRM has a strategic role as a strategic enabler in integrating digital technology with employee competency development. Practices such as e-recruitment, e-learning, Human Resource Information System (HRIS), and data-driven HR have been proven to improve the efficiency, effectiveness, and quality of employee performance. However, the implementation of HRM digitalization still faces various challenges, such as the digital competency gap, resistance to change, and limited organizational readiness and technological infrastructure. In addition, the effectiveness of HRM is influenced by factors such as digital competency, adaptive organizational culture, transformational leadership, and the level of technology adoption. This study concludes that increasing employee productivity in the digital era depends not only on the use of technology but also on the organization’s ability to manage human resources strategically and holistically. This research is limited to the analysis of 15 articles sourced from Google Scholar and SINTA between 2020 and 2026. It is suggested that further research expand the scope of databases, publication periods, and conduct empirical studies to test the relationship between digital HR management practices and employee productivity in more depth